Moral Ecology in Nursing: A Pluralistic Approach - Copeland, Darcy (SAGE Open Nurs, 2019)
Moral dilemmas are present in all settings in which nurses work. Nurses are moral agents who must make moral decisions and take moral action in very complex social systems. Nurses are accountable for their actions, and it is therefore imperative that they have a solid foundation in ethics. There are multiple ethical frameworks nurses can utilize to justify their actions. A theory of moral ecology is presented here as a way to conceptualize the relationships between these frameworks. The first two steps of moral action, moral sensitivity and moral judgment, are explored in a pluralistic context. Specifically, multiple ethical frameworks that inform the practice of nursing are presented using an ecological model. Nurses work in a variety of practice environments, with different populations, across a spectrum of situations. An ecological model acknowledges that nurses are influenced by the complex social, and ethical, systems in which they find themselves taking moral action. When faced with ethical issues in practice, a nurse's moral sensitivity and moral judgment may be guided by ethical systems most proximal to the situation. Nurses bring individual moral beliefs to work and are influenced by the ethical directives of employers, the discipline's code of ethics, principles of bioethics, and various approaches to normative ethics (virtue, consequential, deontological, and care). Any of the frameworks presented may justifiably be applied in various nursing circumstances. I propose that the multiple ethical frameworks nurses utilize exist in a relationally nested manner and a model of moral ecology in nursing is provided.